Insights and issues on the correlation between diffusion and microstructure of saturated cement pastes. (February 2019) - Phung, Quoc Tri; Maes, Norbert; Jacops, Elke; Jacques, Diederik; De Schutter, Geert; Ye, Guang
Abstract: The objective of this study is to quantify the contributions of microstructure and molecular size of diffusing species to tortuosity, constrictivity and effective diffusivity. The microstructural effect is simulated with different sound, leached or carbonated cement pastes with varying water to cement ratios and limestone replacement filler replacements. Leached and carbonated samples were obtained by accelerated experiments: leaching by immersing samples in ammonium nitrate solution and carbonation by subjecting the samples to pure CO2 at elevated pressure. To characterise the microstructural properties, Mercury Intrusion Porosimetry (MIP), and N2 -adsorption were used. The effect of molecular size is quantified with a recent developed diffusion setup allowing for simultaneous measurement of the diffusion of species with different molecular sizes. Previously developed models were also used to verify and give insights into the evolution of diffusion of degraded materials. In addition, a larger dataset from literature is used to evaluate a model which accounts for molecular size as well to predict diffusivity. Resutls show that because of the significant contribution of the molecular size of the diffusing species to the diffusion process, the constrictivity and thereby geometric factor may not be considered as intrinsic properties of the cement pastes. The geometric factor and/or constrictivity of cement pastes depends on the interrelationship of the molecular size of the diffusing species with the microstructure of the cementitious materials. A smaller diffusing species or/and a higher porosity of the sample results in a lower value of geometric factor. Interestingly, constrictivity is significantly influenced by the molecular size, but not the porosity.